2021
DOI: 10.24136/eq.2021.011
|View full text |Cite
|
Sign up to set email alerts
|

Time stability of the impact of institutions on economic growth and real convergence of the EU countries: implications from the hidden Markov models analysis

Abstract: Research background: It is not straightforward to identify the role of institutions for the economic growth. The possible unknown or uncertain areas refer to nonlinearities, time stability, transmission channels, and institutional complementarities. The research problem tackled in this paper is the analysis of the time stability of the relationship between institutions and economic growth and real economic convergence. Purpose of the article: The article aims to verify whether the impact of the instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…These results seem to suggest that investments are particularly effective in fostering economic growth when they support the creation of human capital and the functioning of economic affairs and general public services, which also include basic R&D and the operability of public institutions. While the role of human capital, institutions and R&D in sustaining economic growth is indeed well documented (for a review of relevant literature, see respectively Ogbeifun and Shobande, 2021;Bernardelli et al, 2021;Deleidi and Mazzucato, 2021), economic affairs are directly related to total factor productivity, which is an essential component of economic growth (Carbonari et al, 2013 showed the permanent impact on GDP of an increase in public sector's productivity).…”
Section: Discussionmentioning
confidence: 99%
“…These results seem to suggest that investments are particularly effective in fostering economic growth when they support the creation of human capital and the functioning of economic affairs and general public services, which also include basic R&D and the operability of public institutions. While the role of human capital, institutions and R&D in sustaining economic growth is indeed well documented (for a review of relevant literature, see respectively Ogbeifun and Shobande, 2021;Bernardelli et al, 2021;Deleidi and Mazzucato, 2021), economic affairs are directly related to total factor productivity, which is an essential component of economic growth (Carbonari et al, 2013 showed the permanent impact on GDP of an increase in public sector's productivity).…”
Section: Discussionmentioning
confidence: 99%
“…Institutional quality is our moderating variable. Institutional quality is multifaceted and challenging to define (Bernardelli et al, 2021;Diaz Tautiva et al, 2023;Němečková & Hayat, 2022). Some studies used the Institutional quality index based on five indicators from the International Country Risk Guide's Political Risk Service.…”
Section: Variables Descriptionmentioning
confidence: 99%
“…A majority of studies into regional convergence focus on income convergence (see e.g. Fischer & Pfaffermayr, 2018;Pietrzykowski, 2019;Peshev & Pirimova, 2020;Postiglione et al, 2020;Bernardelli et al, 2021). Papers on convergence in other variables are less common.…”
Section: European Nuts Convergence Studiesmentioning
confidence: 99%